Media Systems in Unrecognized States: “People’s Media” in “People’s Republics” - Kuznetsova, Eugenia (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2023)
This paper examines the media systems in the “Donetsk People’s Republic” and the “Luhansk People’s Republic,” both unrecognized states. After a conflict outbreak in 2014, the media landscape in the unrecognized republics acquired the features of an authoritarian media system. Employing qualitative methods (primary source analysis and in-depth interviews), the research explores a combination of instruments that pushed media into an authoritarian mode that entailed declarations of loyalty, severe vertical subordination, predominantly state ownership, and the designation of a military subdivision at the information frontline. Other decisive factors that allowed an authoritarian media system to be instated are the loyalty of the pre-existing media landscape to local authorities and oligarch media owners, the political isolation of the unrecognized republics, and the strong influence of the Russian information space.